207k views
0 votes
Match each equation with its solution set.

Match each equation with its solution set.-example-1

1 Answer

4 votes

Answer:

Part 1)
a^(2) -9a+14=0 -----> solution set {7,2}

Part 2)
a^(2) +9a+14=0 -----> solution set {-2,-7}

Part 3)
a^(2) +3a-10=0 -----> solution set {2,-5}

Part 4)
a^(2) +5a-14=0 ----> solution set {2,-7}

Part 5)
a^(2) -5a-14=0 ----> solution set {-2,7}

Explanation:

we know that

The formula to solve a quadratic equation of the form


ax^(2) +bx+c=0

is equal to


x=\frac{-b(+/-)\sqrt{b^(2)-4ac}} {2a}

Part 1)

in this problem we have


a^(2) -9a+14=0

so


a=1\\b=-9\\c=14

substitute in the formula


a=\frac{9(+/-)\sqrt{-9^(2)-4(1)(14)}} {2(1)}


a=\frac{9(+/-)√(25)} {2}


a=\frac{9(+/-)5} {2}


a=\frac{9(+)5} {2}=7


a=\frac{9(-)5} {2}=2

The solution set is {7,2}

Part 2)

in this problem we have


a^(2) +9a+14=0

so


a=1\\b=9\\c=14

substitute in the formula


a=\frac{-9(+/-)\sqrt{9^(2)-4(1)(14)}} {2(1)}


a=\frac{-9(+/-)√(25)} {2}


a=\frac{-9(+/-)5} {2}


a=\frac{-9(+)5} {2}=-2


a=\frac{-9(-)5} {2}=-7

The solution set is {-2,-7}

Part 3)

in this problem we have


a^(2) +3a-10=0

so


a=1\\b=3\\c=-10

substitute in the formula


a=\frac{-3(+/-)\sqrt{3^(2)-4(1)(-10)}} {2(1)}


a=\frac{-3(+/-)√(49)} {2}


a=\frac{-3(+/-)7} {2}


a=\frac{-3(+)7} {2}=2


a=\frac{-3(-)7} {2}=-5

The solution set is {2,-5}

Part 4)

in this problem we have


a^(2) +5a-14=0

so


a=1\\b=5\\c=-14

substitute in the formula


a=\frac{-5(+/-)\sqrt{5^(2)-4(1)(-14)}} {2(1)}


a=\frac{-5(+/-)√(81)} {2}


a=\frac{-5(+/-)9} {2}


a=\frac{-5(+)9} {2}=2


a=\frac{-5(-)9} {2}=-7

The solution set is {2,-7}

Part 5)

in this problem we have


a^(2) -5a-14=0

so


a=1\\b=-5\\c=-14

substitute in the formula


a=\frac{5(+/-)\sqrt{-5^(2)-4(1)(-14)}} {2(1)}


a=\frac{5(+/-)√(81)} {2}


a=\frac{5(+/-)√(81)} {2}


a=\frac{5(+)9} {2}=7


a=\frac{5(-)9} {2}=-2

The solution set is {-2,7}

Match each equation with its solution set.-example-1
User Nick Le Page
by
6.4k points